Donor-Derived Myeloid Heme Oxygenase-1 Controls the Development of Graft-Versus-Host Disease - Spilleboudt, Chloé; De Wilde, Virginie; Lewalle, Philippe; Cabanne, Ludovic; Leclerc, Mathieu; Beckerich, Florence; Bories, Dominique; Cardoso, Silvia; Soares, Miguel P.; Vokaer, Benoît; Hougardy, Jean-Michel; Flamand, Véronique; et al. (Frontiers in Immunology, 2021)
Graft-versus-host disease (GVHD) remains a major clinical drawback of allogeneic hematopoietic stem cell transplantation (HSCT). Here, we investigated how the stress responsive heme catabolizing enzyme heme oxygenase-1 (HO-1, encoded by HMOX1) regulates GVHD in response to allogeneic hematopoietic stem cell transplantation in mice and humans. We found that deletion of the Hmox1 allele, specifically in the myeloid compartment of mouse donor bone marrow, promotes the development of aggressive GVHD after allogeneic transplantation. The mechanism driving GVHD in mice transplanted with allogeneic bone marrow lacking HO-1 expression in the myeloid compartment involves enhanced T cell alloreactivity. The clinical relevance of these observations was validated in two independent cohorts of HSCT patients. Individuals transplanted with hematopoietic stem cells from donors carrying a long homozygous (GT)n repeat polymorphism (L/L) in the HMOX1 promoter, which is associated with lower HO-1 expression, were at higher risk of developing severe acute GVHD as compared to donors carrying a short (GT)n repeat (S/L or S/S) polymorphism associated with higher HO-1 expression. In this study, we showed the unique importance of donor-derived myeloid HO-1 in the prevention of lethal experimental GVHD and we corroborated this observation by demonstrating the association between human HMOX1 (GT)n microsatellite polymorphisms and the incidence of severe acute GVHD in two independent HSCT patient cohorts. Donor-derived myeloid HO-1 constitutes a potential therapeutic target for HSCT patients and large-scale prospective studies in HSCT patients are necessary to validate the HO-1 L/L genotype as an independent risk factor for developing severe acute GVHD.